Best practices in animal feed production and management in SAARC countries - Khan, Jasimuddin; SAARC Agricultural Information Centre (Dhaka : SAARC Agriculture Centre, 2008)
Contributed articles.
Includes bibliographical references.
Keywords: Feed processing -- South Asia; Feed processing -- South Asia -- Management